Progressivity of out-of-pocket costs for Medicare-subsidised services and medicines in Australia. - Di Law, Hsei; Marasinghe, Dinith; Biddle, Nicholas; Butler, Danielle; Lancsar, Emily; Desborough, Jane; Korda, Rosemary (International Journal of Population Data Science, 2022)
Objectives In line with affordability and equity principles, Medicare—Australia’s universal public health insurance system—has measures to limit out-of-pocket costs (OOPC), especially among lower income households. We examined the distribution of OOPC for Medicare-subsidised out-of-hospital services and prescription medicines, for Census households, according to their ability to pay. Methods We used 2016 Australian Census data linked to Medicare claims to obtain OOPC for out-of-hospital services and medicines in each household in 2017-18. We derived household disposable income by combining income information from the Census linked to income tax and social security data. All data were available from the Multi-Agency Data Integration Project, enabled through a partnership of various government agencies. We quantified OOPC as a proportion of equivalised household disposable income and calculated Kakwani indices (K) to measure progressivity. We also used linked National Health Survey data to analyse costs separately by chronic conditions. Results We analysed 85% (n=6,830,365) of all Census private households. Overall, OOPC as a percentage of equivalised household disposable income decreased from 1.16% (out-of-hospital services) and 1.35% (prescription medicines) in the poorest decile to 0.63% and 0.34% in the richest decile, respectively. The regressive trend was less pronounced for out-of-hospital services (K = -0.06), with percentage OOPC relatively stable between the 2nd and 9th income deciles; while percentage OOPC decreased steeply with increasing income for medicines (K = -0.24). (Chronic conditions results will be presented—embargoed at time of submission) Conclusion OOPC for out-of-hospital Medicare services were mildly regressive while those for prescription medicines were distinctly regressive. Actions to reduce inequity in OOPC for medicines, such as reducing the co-payments for low income households should be considered.